Grandmaternal effects in preindustrial Lapland - Ylitalo, Elisabeth (My University, 2022)
The grandmother hypothesis proposes that the prolonged post-reproductive lifespan of women has evolved because grandmothers have been able to increase their own inclusive fitness by promoting the lifetime reproductive success of their adult children. Although several studies have provided support for the grandmother hypothesis, there is a lack of studies concerning the association be-tween the female post-reproductive longevity and the number of adult grandchildren, that is, the association between a woman’s post-reproductive lifespan and the lifetime reproductive success of her adult children. Here, I used multigenerational demographic data collected from preindustrial Lapland to investigate 1. whether the lifespan of post-reproductive women was associated with the number of adult grandchildren, 2. whether having a living grandmother affected the survival of her grandchildren, and 3. whether the geographical proximity of the grandmother affected the survival of the grandchildren. I found that the lifespan of post-reproductive women was associated with the number of adult grandchildren: the women gained ten percent more adult grandchildren for every ten years of their post-reproductive lifespan. Moreover, having a living maternal grandmother de-creased the grandchildren’s mortality risk from the age of three onwards, and having a living pater-nal grandmother decreased the grandchildren’s mortality risk from the age of four onwards. The geographical proximity of the maternal grandmother was not associated with the mortality risk of the grandchildren. Altogether, these results provide support for the hypothesis that the prolonged post-reproductive lifespan of women has evolved because grandmothers have promoted the lifetime reproductive success of their adult children and simultaneously their own inclusive fitness.
Keywords: Female post-reproductive lifespan, grandmother hypothesis, lifetime reproductive success, mortality, geographical distance